The posterior capsular central amygdala showing synaptic coactivation with nociplastic pain-associated parabrachial neurons in mice - Takao Okuda; Sawako Uchiyama; Naoko Sato; Yae K. Sugimura; Yukari Takahashi; Makoto Tsuda; Fusao Kato (iScience)
Summary: Projections from the external lateral parabrachial nucleus (elPB) to the central amygdala (CeA) are a key pathway for nociceptive signals and play a crucial role in establishing nociplastic pain sensitization, a state of heightened pain without nociceptor activation or nerve injury. To investigate their roles in nociplastic pain, we aimed to analyze how pain-activated elPB neurons transmit information to pain-activated CeA neurons. Using transgenic TRAP2 mice that underwent transient localized inflammation, we selectively expressed marker proteins, light-sensitive channels, and chemogenetic receptors in pain-activated neurons. We found that the pain-activated (“nociTRAPed”) neurons in the elPB project extensively to the CeA, particularly to the caudal half of the capsular CeA (defined as “posterior CeC” or pCeC), where they form robust functional connections with nociTRAPed pCeC neurons, promoting nociplastic sensitization. We propose that the pCeC serves as the site of direct co-activation with pain-activated elPB neurons, translating peripheral nociceptive information into CeA excitation.